Resiliência e virtudes nas forças policiais: contribuições da Psicologia Positiva - Cacciari, Marcella Bastos (2021)
Literature on police forces usually presents research reports with evaluations of indicators related to the negative impact of this work. In order to broaden the scope of this evaluation and investigate healthy aspects in the police forces, this thesis used positive psychology as a theoretical and methodological lens. Thus, in general, it was evalueted the emotional health of military personnel in different sociocultural contexts and its relationship with resilience, virtues and character strengths in their daily work. In this sense, four studies were produced, which relate to each other to draw this panorama. In Study 1, an integrative literature review was carried out consisting of articles published in the last 10 years. After applied the eligibility criteria, the articles were divided into two groups: 1) research reports on police officers' health (n = 10); and 2) intervention proposals or protocols (n = 12). The results reinforced the importance of describing planned interventions aimed at police resilience. In Study 2, the psychometric properties of the Importance and Perception of Character Strengths Scale (IPCS-Military) in the Brazilian and Portuguese police forces were evaluated. 125 Brazilian military police and 61 Portuguese military officers participated. The internal structure of the inventory scales and the multigroup factorial invariance were evaluated. One-dimensional solutions were confirmed in the two subscales of the inventory, with factorial invariance confirmed. In Study 3, the purpose was to investigate the impact of virtues and character strengths on the resilience of Brazilian and Portuguese military personnel. 125 Brazilian soldiers and 90 Portuguese soldiers participated, who answered an online questionnaire with four scales (Brief Resilience Scale, Importance and Perception of Character Strengths Scale - Military Version, Rosenberg's Self-Esteem Scale, Flourishing Scale) and sociodemographic issues. Descriptives, correlation and regression statistical analyzes were conducted. In the Brazilian sample, the variables self-esteem, perceived strength of persistence and vitality had a direct impact on the model. In the Portuguese sample, the variables self-esteem and perceived strength of perspective were those that most helped to explain resilience. Finally, in Study 4, the emotional health of Brazilian military police officers during a Covid-19 worldwide pandemic was evaluated. The impact of emotional health indicators on police officers' resilience was considered. The participants were 573 Brazilian military police officers who answered an online questionnaire consisting of four scales (Brief Resilience Scale, Post-Traumatic Growth Inventory, Self-Reporting Questionnaire, Flourishing Scale), sociodemographic questions and an open question about emotions experienced during the pandemic period. In relation to qualitative indicators, content analysis and lexical similarity analysis were performed, and, in relation to quantitative indicators, descriptives, correlation and moderation analyzes were performed. The feelings most reported by the participants were connected to the themes: fear of the virus, disappointment with work, emotional distance, emotional exhaustion and life stories. Furthermore, it was found that post-traumatic growth impacts the relationship between flourishing and resilience, indicating that the lower the levels of well-being, the greater the need for post-traumatic growth to achieve resilience as an outcome. In this sense, the clues about paths for new studies and good practices with a focus on promoting the health of police officers are expected.